PENGARUH OLAHRAGA JALAN SANTAI TERHADAP KUALITAS TIDUR LANSIA DI PANTI WERDHA BANDUNG - Elizabeth Ari Setyarini; Ferdinan Sihombing; Veronika Ayu Sandriani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
In the elderly complaints arising from difficulty sleeping at night, where sleep episodes tend to beshort, and almost do not have a deep sleep. If this continues, there is a risk of disturbance in thequality of sleep in the elderly The phenomenon that occurs in the elderly is found 4 out of 5 elderlycomplained of not being able to sleep well at night, during the day often evaporates, noconcentration and the lower conjunctiva looks black. The purpose of this study was to determinethe effect of a relaxing walk on the quality of sleep in the elderly. This research uses quantitativemethods, quasi-experimental design with a pre and post without control approach. The sample ofthis study used a purposive sampling technique, 10 respondents. Instrument for assessing sleepquality: using PSQI. Univariate research results obtained pre-test data that 100% of elderly havepoor sleep quality and post-test results obtained 90% of poor elderly sleep quality and 10% ofgood sleep quality. Paired T-Test samples obtained p value 0,000 <? (0.05 means that there is aninfluence of walking to the quality of sleep in the elderly. Suggestion in this research is to schedulea 3-week walk in the orphanage environment to improve the quality of sleep in the elderly